Effect of Sources and Levels of Dietary Zinc on the Performance, Carcass Traits and Blood Parameters of Broilers - HA Zakaria; M Jalal; HH AL-Titi; A Souad (Brazilian Journal of Poultry Science)
ABSTRACT A total of 400 one-day-old, straight-run, commercial (Ross 308) broiler chicks were used to evaluate the effects of two dietary levels of zinc (Zn) sources on broiler chick performance, carcass traits and blood parameters. Corn-soybean diets were formulated for three rearing phases (starter, grower and finisher). The two dietary treatments applied consisted of the addition per kg of diet of 80mg of inorganic Zn (ZnO) (T1), or 80mg of ZnO plus 42mg of an organic Zn-amino acid complex (Availa-Zn120; Zinpro Corporation, Eden Prairie, MN, USA), totaling 122mg of the combined organic and inorganic Zn sources (T2). Birds were distributed according to a completely randomized design in the two treatments with eight replicates (pens) of 25 birds each. Feed and water were provided ad libitum. On day 42, blood samples were taken from four birds closest to the group average weight per replicate (32 per treatment) and then slaughtered for carcass evaluation. The results of this study did not find any significant effect of either of the evaluated Zn sources on broiler growth performance. Mortality rate was significantly lower (p<0.05) by the higher Zn concentration and the Zn sources group (T2). Carcass yields were not significantly influenced by the treatments. Breast quality showed significant improvement (p<0.05) in shear force (T2), indicating juicier meat. Higher concentrations (p<0.05) of Zn, Phosphorus (P), and total protein in blood were noted in (T2). Birds fed a mixture of organic and inorganic Zn source (T2) presented overall better results.